Fait social dans le roman Un Sac de Billes de Joseph Joffo: une étude sociologique de la littérature par Émile Durkheim - Sela Setyaningtyas, Aisya; Novi Kuniawati; Sunahrowi; Marliza Arsiyana (Lingua Litteria Journal, 2024)
Un Sac de Billes is among Joseph Joffo's renowned novels, recounting the harrowing journey of Jewish individuals, Joseph and Maurice, as they flee to the free zone in Menton. However, their escape is fraught with challenges. This study aims to elucidate the social realities and solidarity prevalent during that era, drawing from Emile Durkheim's theories. The research focuses on the French novel of the same title and employs listening and note-taking techniques to gather data. Through data analysis, 17 instances were identified, encompassing (1) tangible social realities, totaling 10 instances, such as the Yellow Star badge, the presence of German soldiers, and posters; (2) intangible social realities, totaling 5 instances, each reflecting prevailing opinions and viewpoints of the time; and (3) instances of mechanical solidarity, comprising 2 instances highlighting the shared experiences between characters, specifically their Jewish identity.